BUNUH DIRI SINYALEMEN LEMAHNYA AQIDAH UMMAT (TUGAS URGEN DA’I DALAM PEMANTAPAN AQIDAH) - M. Amin Sihabuddin (Fakultas Dakwah dan Komunikasi, Universitas Islam Negeri, Raden Fatah Palembang, 2012)
Suicide among Muslims is a sign or characteristic (indication) has not committed and the faith’s or their creed.So in the face of problems, especially problems for killing or murder five basic needs, ie., Fa'ali (eating, drinking and sexual), peace and security, the need for attachment to the group, a sense of respect and the need for achievement of goals. The condition of weak faith as a legacy of the ancestors or taqlid surely can not be the solutions to the problems they face (suicidal acts), plus the birth of despair or frustration toward destiny God Almighty, and yet can reap the wisdom of a disaster or his temptation to be a cumulative problem of suicide itself.Faith such a way to be understood by the preachers to bring the people as a mediator for the audience to be patient and sole trust and can provide insights on improving the quality of faith developing and people preaching a message form must be rational - logical - religious and can guide your heart and soul they worship only Him alone. The task of this noble Prophet and his Companions had played in islamic preaching activity of Makkah period.